Protective and connective professionalism: What we have learned and what we still would like to learn. Issue 2 (31st July 2021) - Noordegraaf, Mirko; Brock, David M
Abstract: This essay begins with a contribution from Mirko Noordegraaf, author of the 2020 'From Protective to Connective Professionalism' article that initiated this series of exchanges in the Journal of Professions and Organization ( JPO ). Then, wrapping up this series, David Brock, JPO Editor-in-Chief, looks back at protective and connective constructs in our literature, and suggests several research directions. Our aim is not to close the debate, but to open it up and connect it to promising research avenues, newly arising research strands and promising publications.